Is Renewable Energy Really Green? - Pillai, Kamala Vainy (Forbes Opinion, 2014)
The global green rush to move away from fossil fuel dependence has incontestably led to a plethora of renewable energy initiatives – some sounding sexier and more appealing than others. From the traditional renewable energy like hydropower, wind, solar and biofuel, today’s alternative renewable energies using disruptive technologies promises innumerable avenues for a host of communities and nations. Anaerobic digestion energy, biomass, geothermal, ocean energy such as ocean thermal, tidal or wave energy, solar thermal and tower power technologies are already joining the bandwagon of emerging stars. Yet, are Renewables really green?